2016
DOI: 10.1016/j.biopsych.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Human Striatum in Tourette Syndrome

Abstract: Background: Genome wide association studies have not revealed any risk-conferring common genetic variants in Tourette syndrome (TS), requiring the adoption of alternative approaches to investigate the pathophysiology of this disorder. Methods: We obtained the basal ganglia transcriptome by RNA sequencing in the caudate and putamen of 9 TS and 9 matched normal controls. Results: We found 309 down-regulated and 822 up-regulated genes in the caudate and putamen (striatum) of TS individuals. Using data-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
195
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(207 citation statements)
references
References 69 publications
11
195
1
Order By: Relevance
“…Postmortem studies show a reduction in ChAT-expressing striatal interneurons in the caudate and putamen in individuals with severe, refractory disease (26,27). However, such correlational findings cannot elucidate the causal role of this cellular deficit: whether it is pathogenic, compensatory, epiphenomenomenal, or a marker of a more complex developmental disruption.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Postmortem studies show a reduction in ChAT-expressing striatal interneurons in the caudate and putamen in individuals with severe, refractory disease (26,27). However, such correlational findings cannot elucidate the causal role of this cellular deficit: whether it is pathogenic, compensatory, epiphenomenomenal, or a marker of a more complex developmental disruption.…”
Section: Discussionmentioning
confidence: 98%
“…The ChAT interneurons may fail to develop or differentiate properly, fail to migrate to the striatum during development, migrate but die without integrating properly into the striatal circuitry, or develop and integrate normally but die (or dedifferentiate) at a later time. Inflammatory damage to them is an interesting possibility, given recent evidence for an elevated inflammatory state in the TS striatum (27,53), but this remains speculative. The development of preventative or disease-modifying therapeutics targeting the cholinergic deficit will be facilitated by clarification of its etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one important area that is largely missing concerns the findings from post-mortem studies of the brains of individuals with TS that have been conducted by Flora Vaccarino and her laboratory at Yale University. The most notable and highly-cited article from 2016 presents an analysis of the transcriptome of striatal tissue (caudate and putamen) from the brains of nine TS and nine matched normal control subjects (Lennington et al, 2016 1 ). The authors found 309 down-regulated and 822 up-regulated genes using a data-driven gene network analysis.…”
mentioning
confidence: 99%